Experimental and FEM Investigation of Cob Walls under Compression - Enrico Quagliarini; Gianluca Maracchini (Advances in Civil Engineering)
Earth has been used as construction material since prehistoric times, and it is still utilized nowadays in both developed and developing countries. Heritage conservation purposes and its intrinsic environmental benefits have led researchers to investigate the mechanical behaviour of this material. However, while a lot of works concern with rammed earth, CEB, and adobe techniques, very few studies are directed towards cob, which is an alternative to the more diffused rammed earth and adobe in specific geographic conditions. Due to this lack, this paper presents an experimental program aimed at assessing the failure mode and the main mechanical properties of cob earth walls (compressive strength, Young’s modulus, and Poisson’s ratio) through monotonic axial compression tests. Results show that, if compared with CEB, adobe, and rammed earth, cob has the lowest compressive strength, the lowest modulus of elasticity, and Poisson’s ratio. Differences are also found by comparing results with those obtained for other cob techniques, underlining both the high regional variability of cob and the need of performing more research on this topic. A strong dependence of material properties on loading rate and water content seems to exist too. Finally, the ability of a common analytical method used for masonry structures (an FEM macromodelling with a total strain rotating crack model) to represent the mechanical behaviour of cob walls is showed.